المركز الثقافي للزاوية التجانية بقمار ودوره الدعوي - ربيعي, صابرة (University of Eloued جامعة الوادي, 2017)
تهدف هذه الدراسة إلى التعرف على المركز الثقافي للزاوية التجانية بقمار و أهم نشاطاته وإسهاماته في الجانب الدعوي بصفة خاصة والجانب العلمي والثقافي والاجتماعي بصفة عامة، كما هدفت الدراسة أيضا إلى التعرف على أهم النشاطات المقدمة لرواد المركز الثقافي من طلبة وباحثين وغيرهم، محاولين بذلك عرض ما تم عقده في المركز من ملتقيات ومحاضرات وأيام دراسية وتكوينية. وقد قسمت هذه الدراسة إلى أربعة فصول، الفصل الأول يوضح الإطار المنهجي للدراسة، والفصل الثاني يقدم لمحة عن الزاوية التجانية بقمار، والفصل الثالث جعلته للتعريف بالمركز الثقافي، والفصل الرابع خصصته للإسهامات الدعوية للمركز الثقافي. The aim of the study was to identify the cultural center of Al-Zawyat Al-Tijaniyya and its activities and its contribution to the educational aspect in particular, and the scientific, cultural and social aspects in general. The study also aimed to identify the most important activities offered to students, researchers and othersby the cultural center. The activities included lectures, seminars and training days. The first chapter consists of the methodological framework of the study .The second chapter presents a brief overview of the Al-Zawyat Al-Tijaniyya , the third chapter includes the presentation of the cultural center, and the fourth chapter explains the religious contributions of the cultural center
مذكرة ماستر تخصص دعوة واعلام
Keywords:  المركز الثقافي.  الزاوية التجانية.  الدعوة; Center Culture ــــ Al-Zawyat Al-Tijaniyya ـــ Preaching (Daawa